Enhancing Above-Knee Prosthetic Design for Inclusive Workplaces: Ergonomic Considerations in Manual Material Handling - Khoirul Muslim; Adinda Shafira; Rifko Rahmat Kurnianto; Sandro Mihardi; Auditya Purwandini Sutarto (Jurnal Optimasi Sistem Industri)
Employment is crucial for economic sustainability and social inclusion, yet individuals with disabilities face significant barriers. Globally, only 44% of disabled individuals are employed compared to 75% of those without disabilities. Manual material handling (MMH) relies heavily on stability and control in demanding industries such as manufacturing and logistics. Such demands create challenges for individuals with above-knee prostheses, as most current designs focus on walking and do not adequately support the postural and load-bearing requirements of MMH tasks. This study aims to evaluate the performance of transfemoral prosthesis designs during MMH, analyzing the effects of container type, load mass, and their interaction on gait efficiency, discomfort, and stability. Eight male unilateral above-knee amputees (24–39 y) carried handled and handle-less boxes loaded from 4 to 10 kg in a randomised within-subject trial. Gait deviation, perceived discomfort, and steadiness were captured with self-report measures. Two-way analysis of variance analyses showed a significant container × load interaction: handle-less 10 kg loads produced the greatest lateral trunk lean toward the prosthetic side, whereas lighter handled loads minimised deviation. Increasing load also elevated discomfort in the back, waist, stump and contralateral arm and reduced perceived stability. Observed lateral lean and impact-related knee extension suggest three priority modifications: (1) add socket adduction within an ischial-containment design to improve femoral stabilisation, (2) increase knee-swing friction to soften terminal impact, and (3) fit dual-keel feet to cushion heel strike. Implementing these changes may reduce gait errors and fatigue, raising safe lifting capacity for transfemoral prosthesis users in MMH task. Nonetheless, the male-only sample may not capture gender-specific gait strategies; future trials should include female participants and a larger cohort to verify generalisability. These preliminary findings still offer insights into improving prosthetic designs to enhance safety, functionality, and inclusion in industrial MMH tasks.